Mixed convection in a lid-driven cavity containing triangular block with constant heat flux: Effect of location of block - Gangawane, Krunal M.; Öztop, Hakan Fehmi; Ali, Mohamed E. (Pergamon-Elsevier Science Ltd, 2019)
The present work examines the two-dimensional, steady, laminar mixed convective fluid circulation and heat transfer in a square lid-driven cavity influenced by the change in the location of the triangular block with constant heat flux (CHF) thermal condition. The effect of the changes in the location of block along the vertical centerline (x = 0.5, y) of the cavity has been explored. The dependence of various flow governing dimensionless parameters, such as, Reynolds number (Re = 1 - 1000), Richardson number (Ri = 0.01, 1, 10), blockage (B = 0.1, 0.2, 0.3) and location (L-y = 0.25,0.5, 0.75) of triangular block on the streamline, temperature contours, Nusselt numbers, etc. has been illustrated. A normalized Nusselt number is also calculated for studying the difference in heat transfer rate with that of constant wall temperature condition. The results of the study indicates higher heat transfer rates for centered block position (L-y = 0.5) than remaining two (L-y = 0.25, 0.75). For a given blockage, Nusselt number shows decline with increasing Ri. The summary of research is expressed by using two forms of empirical correlations ((Nu) over bar = f (L-y, Re)), (Nu) over bar = f (B, Re) for for possible utilization in engineering design.
Keywords: Mixed convection; Triangular block; Lid-driven cavity; Richardson number; Constant heat flux; SIMPLE; Finite volume method